Functional Outcome of Limb Salvage Surgery With Megaprosthesis In Primary Bone Tumour Arround Knee - Misbahuddin Misbahuddin; Mujaddid Idulhaq (Eduvest - Journal of Universal Studies, 2023)
The knee is the most frequent site of primary bone tumour. A majority of the tumours arising in the knee can be treated with limb salvage surgery and result in good functional outcomes. We evaluated functional outcomes for patients who underwent surgery for resection and megaprosthesis replacement for primary tumours around the knee. We used the Musculoskeletal Tumour Society Scoring System (MSTS) for functional evaluations to compare differences between distal femur and proximal tibia placements. This study was an observational analysis study with cross sectional approach in primary bone tumor knee region which has been done limb salvage surgery. The study sample included 11 cases of distal femur and 6 cases of proximal tibia megaprosthesis replacement. Primary tumours were classified as follows: 5 osteosarcoma, 12 giant cell tumour (GCT). The Patients was subjected to a physical examination to complete MSTS score and then commpared data were obtained. Functional outcomes, as measured by MSTS functional assessment were good to excellent in a majority of study patients. This study shows an unsignificant differences functional outcome using MSTS Score between resection tumour in distal femur and proximal tibia (p >0.05). There were no differences in functional outcomes when comparing distal femur megaprostheses with proximal tibia megaprostheses